2016
DOI: 10.1182/blood-2015-11-681494
|View full text |Cite
|
Sign up to set email alerts
|

Limiting hepatic Bmp-Smad signaling by matriptase-2 is required for erythropoietin-mediated hepcidin suppression in mice

Abstract: Key Points• Hyperactivation of the BMP-SMAD pathway blunts EPO-mediated hepcidin inhibition.• Lack of BMP-SMAD pathway inhibition by matriptase-2 abrogates the ERFEmediated hepcidin suppression in response to EPO.Hepcidin, the main regulator of iron homeostasis, is repressed when erythropoiesis is acutely stimulated by erythropoietin (EPO) to favor iron supply to maturing erythroblasts. Erythroferrone (ERFE) has been identified as the erythroid regulator that inhibits hepcidin in stress erythropoiesis. A power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
96
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 38 publications
(44 reference statements)
11
96
0
1
Order By: Relevance
“…Genetic inactivation of TMPRSS6 preserved the iron overload of Hjv − / − mice, supporting the notion that HJV is a likely substrate for TMPRSS6 (Finberg et al, 2010). Genetic experiments further indicate that TMPRSS6 requires functional BMP6/SMAD signaling for its activity (Nai et al, 2016). EPO was tested as a therapeutic for IRIDA.…”
Section: Controlling Supply and Demand: Iron Acquisition For Red Bloomentioning
confidence: 99%
“…Genetic inactivation of TMPRSS6 preserved the iron overload of Hjv − / − mice, supporting the notion that HJV is a likely substrate for TMPRSS6 (Finberg et al, 2010). Genetic experiments further indicate that TMPRSS6 requires functional BMP6/SMAD signaling for its activity (Nai et al, 2016). EPO was tested as a therapeutic for IRIDA.…”
Section: Controlling Supply and Demand: Iron Acquisition For Red Bloomentioning
confidence: 99%
“…Previous studies have shown that hepcidin production was not affected by EPO in Tmprss6 mutant mice 4 . More recently, Nai and colleagues suggested that matriptase-2 may act downstream of EPO to dampen the signaling through the BMP-Smad regulatory pathway and allow ERFE to repress hepcidin production 5 . We therefore examined the crosstalk between ERFE and matriptase-2 in mice.…”
Section: Correspondencementioning
confidence: 99%
“…Similarly, deleting Tmprss6 , which encodes a serine protease that represses hepcidin expression, causes decreased liver non‐haem iron concentration and decreased mean corpuscular volume; however, Tmprss6 knockout mice developed a more severe phenotype than Smad7 Alb/Alb mice 38. In addition, a recent study suggested that Tmprss6 plays a key role in erythroferrone‐mediated hepcidin suppression 39. In contrast, hepatic expression of Tmprss6 remains unchanged in our Smad7 Alb/Alb mice (Figure S3).…”
Section: Discussionmentioning
confidence: 99%